2014
DOI: 10.1126/science.1258168
|View full text |Cite|
|
Sign up to set email alerts
|

On the origin of near-infrared extragalactic background light anisotropy

Abstract: Extragalactic background light (EBL) anisotropy traces variations in the total production of photons over cosmic history, and may contain faint, extended components missed in galaxy point source surveys. Infrared EBL fluctuations have been attributed to primordial galaxies and black holes at the epoch of reionization (EOR), or alternately, intra-halo light (IHL) from stars tidally stripped from their parent galaxies at low redshift. We report new EBL anisotropy measurements from a specialized sounding rocket e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
254
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(271 citation statements)
references
References 55 publications
15
254
2
Order By: Relevance
“…and Zemcov et al (2014) suggested that "orphan" stars at z ∼ 1 − 5 in a diffuse intrahalo light could fully explain the detected excess CIB fluctuation. Our measurement of the CIB vs CXB coherence means that intra-halo light could produce most of the CIB excess only if a substantial fraction (larger than that observed in galaxies) of the orphan stars are X-ray binaries or pulsars or share the same environment with hot X-ray emitting gas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Zemcov et al (2014) suggested that "orphan" stars at z ∼ 1 − 5 in a diffuse intrahalo light could fully explain the detected excess CIB fluctuation. Our measurement of the CIB vs CXB coherence means that intra-halo light could produce most of the CIB excess only if a substantial fraction (larger than that observed in galaxies) of the orphan stars are X-ray binaries or pulsars or share the same environment with hot X-ray emitting gas.…”
Section: Discussionmentioning
confidence: 99%
“…This Diffuse Galactic Light is very faint at 3.6 and 4.5 µm, and is generally estimated through extrapolation from, or cross correlation with, much brighter interstellar emission at other wavelengths (e.g., Kashlinsky et al 2005;Arendt et al 2010;Zemcov et al 2014;Matsumoto et al 2011;Seo et al 2015). Galactic X-rays also scatter in the diffuse ISM (Molaro et al 2014) and thus might correlate with the IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird et al (2016) discuss how the observed detection rate, inferred from the so 4 We limit the range to where there is overall consistency between the CIB fluctuation results from various instruments (AKARI and Spitzer) and analyses. The situation at 1-1.6 μm is contradictory as discussed in detail in Kashlinsky et al (2015b, Section 2.1.2): conflicting levels have been measured by, on the one hand, the mutually consistent (at the same depth) deep 2MASS (Kashlinsky et al 2002;Odenwald et al 2003) and NICMOS (Thompson et al 2007a(Thompson et al , 2007b analyses and, on the other, the much shallower CIBER (Zemcov et al 2014) data. far single published event, can be made consistent with that expected from the PBHs making up the DM such that their comoving mean mass density, assumed constant since their formation until at least their possible later evolution (discussed in Section 4 and references therein), is given by Below we will assume, for simplicity, that all PBHs have identical mass.…”
Section: Pbhs Small-scale Mass Fluctuation Power and First Object Cmentioning
confidence: 99%
“…And the unexpected discovery by the Cosmic Infrared Background ExpeRiment (CIBER) rocketborne experiment of powerful emission in the near IR from the peripheries of galaxies and from intergalactic space (Zemcov, et al (2014)) is evidently a manifestation of neglected fine dust. Thus, it is possible that up to now the spatial mass density of all dust (and not just the coarse dust) has been underestimated.…”
Section: Coarse Dust Outside the Galactic Diskmentioning
confidence: 99%